1999
DOI: 10.1017/s0029665199000592
|View full text |Cite
|
Sign up to set email alerts
|

Optimal nutrition: vitamin A and the carotenoids

Abstract: There are two major dietary sources of vitamin A: easily absorbed retinyl palmitate in foods of animal origin, and poorly bioavailable carotenoids from plant foods. Plasma retinol is tightly controlled, probably by regulation of retinol-binding protein (RBP) formation in the liver, and only hormonal factors (e.g. oral contraceptives) and infection will alter the homeostasis. Delivery of retinol to the tissues is facilitated by the RBP-retinol complex; however, there is evidence that this mechanism can be bypas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 48 publications
2
26
1
1
Order By: Relevance
“…Furthermore, while liver retinol significantly increased during the repletion period (except for parsley), plasma retinol did not increase during this period due to any treatment. These results are in agreement with Thurnham and Northrop-Clewes (1999), who suggested that there is no relation between retinol content in plasma and diet, unless the liver retinol pool is depleted noticeably. It seems that a homeostatic process is involved in maintaining the retinol levels in plasma, despite the retinol depletion in liver, as suggested by Zacaria-Rungkat et al (2000).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, while liver retinol significantly increased during the repletion period (except for parsley), plasma retinol did not increase during this period due to any treatment. These results are in agreement with Thurnham and Northrop-Clewes (1999), who suggested that there is no relation between retinol content in plasma and diet, unless the liver retinol pool is depleted noticeably. It seems that a homeostatic process is involved in maintaining the retinol levels in plasma, despite the retinol depletion in liver, as suggested by Zacaria-Rungkat et al (2000).…”
Section: Discussionsupporting
confidence: 93%
“…Breast milk concentrations of lutein and zeaxanthin appear to differ greatly between individuals, as is also seen in plasma (Thurnham & Northrop-Clewes, 1999). Jackson et al (1998) and Macias and Schweigert (2001) also reported a high between-subject variation in his study of milk carotenoid concentrations.…”
Section: Discussionmentioning
confidence: 85%
“…The results of this study indicate that there were no differences between vegetarians and omnivores in the level of cellular endogenous antioxidants, such as in the activities of GPX, SOD and GST in erythrocyte, in the level of GSH in erythrocytes and in the plasma levels antioxidants nutrients (vitamin C, retinol and a-tocopherol) despite the increased dietary intakes of these antioxidants by the vegetarian group. The reason for the lack of difference in the antioxidant vitamin status between the two groups might partly be due to homeostasis and/or saturation of retinol and a-tocopherol (Thurnham and Northrop-Clewes, 1999), and partly to plasma vitamin C level reflecting current vitamin C intake rather than the habitual intake (Bates and Thurnham, 1997). Moreover, since this was a 'convenient cohort', the healthy volunteer effect, particularly in the omnivore group could not be ruled out.…”
Section: Discussionmentioning
confidence: 99%